2014
DOI: 10.1053/j.semnuclmed.2013.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Urogenital Diseases

Abstract: There is an expanding and exciting repertoire of PET imaging radiotracers for urogenital diseases, particularly in prostate cancer, renal cell cancer, and renal function. Prostate cancer is the most commonly diagnosed cancer in men. With growing therapeutics options for the treatment of metastatic and advanced prostate cancer, improved functional imaging of prostate cancer beyond the limitations of conventional computed tomography (CT) and bone scan (BS) is becoming increasingly important for both clinical man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 144 publications
0
22
0
2
Order By: Relevance
“…Radiotracers that have received attention for this purpose include 11 C-choline, 18 F-fluoroethylcholine, 18 F-FACBC, and a host of molecules targeting prostate-specific membrane antigen (PSMA; also known as glutamate carboxy-peptidase) such as 68 Ga-PSMA-11 and 18 F-DCFPyL 61,62 . PSMA-targeted imaging has gained particular interest, as radiotracers targeting this cell surface protein have been shown in numerous reports to offer outstanding sensitivity for detecting small-volume sites of prostate cancer that are not detectable on conventional imaging 63 (FIG.…”
Section: Imaging Of Oligometastatic Prostate Cancermentioning
confidence: 99%
“…Radiotracers that have received attention for this purpose include 11 C-choline, 18 F-fluoroethylcholine, 18 F-FACBC, and a host of molecules targeting prostate-specific membrane antigen (PSMA; also known as glutamate carboxy-peptidase) such as 68 Ga-PSMA-11 and 18 F-DCFPyL 61,62 . PSMA-targeted imaging has gained particular interest, as radiotracers targeting this cell surface protein have been shown in numerous reports to offer outstanding sensitivity for detecting small-volume sites of prostate cancer that are not detectable on conventional imaging 63 (FIG.…”
Section: Imaging Of Oligometastatic Prostate Cancermentioning
confidence: 99%
“…More recently, 18 F-flouride PET/CT has been found to have improved sensitivity and specificity for sites of osseous metastatic involvement. Studies have demonstrated improved accuracy of 18 F-Flouride PET/CT over MDP SPECT/CT in PCa [5759]. Increased fluoride uptake in malignant bone lesions reflects the increase in regional blood flow and bone turnover characterizing on bone metastases.…”
Section: Psma Pet In Primary Stagingmentioning
confidence: 99%
“…Positron imaging tomography (PET) with 2-deoxy-2-[ 18 F]fluoro-D-glucose ([ 18 F]FDG) has been used to detect PCa [2], but due to low sensitivity and overlap with prostatitis, prostatic hypertrophy, and radiotracer renal secretion and accumulation in the bladder, new PET radiotracers are highly desired [3]. Choline PET imaging, using [ 11 C]choline or [ 18 F]fluoroethylcholine, is more sensitive for detecting PCa than [ 18 F]FDG [47].…”
Section: Introductionmentioning
confidence: 99%